Effect of supplementation frequency in feeding behavior, displacement patterns and forage intake of beef heifers - Maria José de Oliveira Sichonany (Semina: Ciências Agrárias, 2017)
Our work was carried out to evaluate forage intake, feeding behavior and displacement patterns of beef heifers fed exclusively on pasture or receiving oat grain, either daily (“frequent”) or from Monday to Friday (“infrequent”), in two phenological stages of Alexandergrass ( Urochloa plantaginea Link.): “Vegetative” and “Reproductive”. The grazing method was continuous, with a variable number of animals. The experimental design was completely randomized with measures repeated in time with three feeding frequencies and two phenological stages. Forage intake was estimated using the chromic oxide technique as an indicator of fecal output. Heifers on exclusive Alexandergrass pasture and frequently supplemented had higher forage intake of dry matter (DM, 2.91 kg DM 100 kg BW -1 ) than those that were infrequently supplemented (2.00 kg DM 100 kg BW -1 ). Forage intake was greater in the “Vegetative” stage. The use of feeding stations is modi¿ed in response to supplementation frequency and phenological stages of Alexandergrass. Bite mass was higher for daily supplemented heifers, and these animals spent less time grazing. Also, bite mass was the item that best explained DM total ingestion. Bite mass and grazing time were similar throughout the phenological stages, whereas bite rate decreased in the reproductive stage. Feeding behavior and forage intake responses of beef heifers were inÀuenced by supplementation frequency and phenological stages of Alexandergrass.